2022
DOI: 10.1021/acsaem.2c02068
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-Based Composite Films with Largely Enhanced Energy Storage Performances toward High-Temperature Electrostatic Capacitor Applications

Abstract: The next generation of high-energy-density electrostatic capacitors operable under elevated temperatures is urgently demanded to cope with the development of advanced high-power electronic systems. However, the inherent characteristics of the existing polymer dielectrics, such as poor heat dissipation, narrow band gaps, and high conduction loss, limit their energy density at high temperatures and result in a major hindrance to their applications under harsh conditions. Herein, a class of sandwich-structured di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Figure a illustrates the comparison of U e and η of PI/BNNS film with reported PI dielectric materials, including intrinsic PI, , PI nanocomposites, all-organic PI composites, ,, multilayer-structured PI composites, , and PI composites containing inorganic layer. ,, The blue, gray, yellow, purple, and green boxes are used to classify the above materials on the right of Figure a. It is found that the PI/BNNS film achieves the maximum U e when η is greater than 90%, which is far superior to the reported PI-based dielectric materials at different temperatures.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure a illustrates the comparison of U e and η of PI/BNNS film with reported PI dielectric materials, including intrinsic PI, , PI nanocomposites, all-organic PI composites, ,, multilayer-structured PI composites, , and PI composites containing inorganic layer. ,, The blue, gray, yellow, purple, and green boxes are used to classify the above materials on the right of Figure a. It is found that the PI/BNNS film achieves the maximum U e when η is greater than 90%, which is far superior to the reported PI-based dielectric materials at different temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…The area of the PI/BNNS-2 film decreases slightly with the increase in temperature, revealing high temperature stability of capacitive performance. Figure 6a illustrates the comparison of U e and η of PI/ BNNS film with reported PI dielectric materials, including intrinsic PI, 14,39 PI nanocomposites, 40−44 all-organic PI composites, 15,45,46 multilayer-structured PI composites, 47,48 and PI composites containing inorganic layer. 28,29,49−52 The blue, gray, yellow, purple, and green boxes are used to classify the above materials on the right of Figure 6a.…”
Section: Acsmentioning
confidence: 99%
“…22 Among them, PEI has been widely acknowledged to be the appropriate linear dielectric for preparing the high-temperature dielectric capacitors owing to its excellent thermal stability and high glass transition temperature. 5,13,23 However, according to the Schottky injection formula, the injections and movements of charge carriers become active with increased temperature, which inevitably intensify material deformation. 17 Meanwhile, the conjugated segments in PEI endow the carriers with high conduction at high electric field, resulting in drastically increased conduction loss with the coupling effect of high-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband nanofillers such as SiO 2 , Al 2 O 3 , TiO 2 , BNNs, CaF 2 , and MgO have been shown to enhance the electrical properties of polymers at high temperatures when compounded with polymers. Wang et al investigated the electrical properties of MgO/PI nanocomposites with different morphologies and demonstrated that the high specific surface area of MgO nanosheets could enhance the electrical properties of the composites to a greater extent. The two-dimensional morphology better impedes carrier migration at high temperatures and significantly reduces the composite leakage current, resulting in superior electrical performance and energy storage density .…”
Section: Introductionmentioning
confidence: 99%